Contract worker unrest at Wistron Infocomm Manufacturing (India) Pvt Ltd - Varkkey, Biju, (SAGE Business cases., 2024)
The case study concerns a multinational company, Wistron Corporation (WC). WC was incorporated on May 30, 2001 and is headquartered in Taipei city of Taiwan. It is a technology service provider to companies like Apple, Microsoft, HTC, Lenovo, Sony Xiaomi, Dell, HP and more. As per a media report in 2017, Apple Inc contracted WC to manufacture iPhones in India under the ‘Make in India’ initiative by the Government of India (GoI). WC created a wholly-owned subsidiary WIMPL to undertake operations in India. The case highlights how WIMPL’s functioning was hampered due to non-adherence to the local laws of the land, and the unethical treatment of contract workers. WIMPL’s Narasapura facility commenced its operations with an initial workforce of 2000 workers during May 2020. The facility had quadrupled its workforce to around 9,833 as of December 2020, of which, around 8,490 were contract workers and around 1,343 were permanent employees. These contract workers were employed through various staffing agencies. WIMPL employed more contract workers than was legally permitted. The case study discusses various events where WIMPL and the staffing agencies were non-responsive to the grievances of the contract workers. As a result, a feeling of discontent had been brewing among the contract workers. Later, on December 12, 2020, when once again the grievances of the contract workers were left unaddressed, they retaliated with a violent outburst, damaging company property. Many industrial associations and the state government came in support of WIMPL. A few trade unions and sections of media supported the workers. WIMPL initially claimed that it had abided by all local laws. However official investigations by the state labour department i.e. Department of Factories, Boilers, Industrial Safety & Health (DFBISH) confirmed that WIMPL had violated many local laws relating to wage payment, wage delays and payment of overtime. The report also confirmed that the rapid increase